TINJAUAN HUKUM ISLAM TERHADAP IKHTILATH DALAM TEMPAT KERJA (STUDI KASUS DI PT. SEJAHTERA UTAM SOLO) - Romadhon, Rahmad; Syamsuddin, S; Baihaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
would not die, greater slander for men. ikhtilath occurs in markets, buses, schools, workplaces, and many more, it is very very unfortunate that this happens and is even done by a Muslim himself, so this is a problem that must be of concern to all Muslims, judging from its impact, ikhtilath is the beginning from the act of adultery and this often happens in the workplace where they spend their days at the workplace, at work they can chat with anyone whether it's a man or a woman, so this research is interested in conducting this research, research on Islamic Law Review Against Ikhtilath in the World of Work Case Studies at PT Sejahtera Utama Solo, in this study the researchers used Field Research (field research) and Library Research (field research) with a qualitative approach, namely an approach that produces exposure in the field and then the description will be analyzed from legal aspect. The results of the study show that there are still elements of sincerity in the work environment of PT. Sejahtera Utama Solo in the form of physical contact with the opposite sex, crowds between men and women. The view of local religious leaders is of the opinion that ikhtilath in the world of work is actually ikhtilath which is permissible due to the benefits obtained and can become ikhtilath which is forbidden if there are elements of ikhtilath such as touching , looking at it with lust, to overcome the occurrence of ikhtilath there must be a separator between men and women if possible, accompanied by guidance on the dangers of ikhtilath.